Early-life stress induces persistent alterations in 5-HT1A receptor and serotonin transporter mRNA expression in the adult rat brain - Bravo, Javier A.; Dinan, Timothy G.; Cryan, John F. (Frontiers in Molecular Neuroscience, 2014)
Early-life experience plays a major role in the stress response throughout life. Neonatal maternal separation (MS) is an animal model of depression with an altered serotonergic response. We hypothesize that this alteration may be caused by differences in 5-HT1A receptor and serotonin transporter (SERT) mRNA expression in brain areas involved in the control of emotions, memory and fear as well as in regions controlling the central serotonergic tone. To test this, Sprague-Dawley rats were subjected to MS for 3h daily during post-natal days 2-12. As control, age matched rats were not separated (NS) from their dams. When animals reached adulthood (11-13 weeks) brain was extracted and mRNA expression of 5-HT1A receptor in amygdala, hippocampus and dorsal raphé nucleus (DRN) and SERT in the DRN was analyzed through in-situ hybridisation. Densitometric analysis revealed that MS increased 5-HT1A receptor mRNA expression in the amygdala, and reduced its expression in the DRN, but no changes were observed in the hippocampus in comparison to NS controls. Also, MS reduced SERT mRNA expression in the DRN when compared to NS rats. These results suggest that early-life stress induces persistent changes in 5-HT1A receptor and SERT mRNA expression in key brain regions involved in the development of stress-related psychiatric disorders. The reduction in SERT mRNA indicates an alteration that is in line with clinical findings such as polymorphic variants in individuals with higher risk of depression. These data may help to understand how early-life stress contributes to the development of mood disorders in adulthood.